KEDUDUKAN AS-SUNNAH DAN TANTANGANNYA DALAM HAL AKTUALISASI HUKUM ISLAM (Mazahib, 2015)
Sunnah of the Prophet Muhammad that had been understood by the majority of Muslims as role models; in the form of words, deeds / actions and the approval of the actions of others by the Prophet must always be understood in a dynamic and lively way. When Sunnah is understood as an ijtihad of the Prophet Muhammad in interpreting and applying the revelation / word of Allah in religious life and society, then following the sunnah of the Prophet became a major force in encouraging the creation of dynamic progress, inspiration and innovation. But if the sunnah of the Prophet is understood and translated literally, the sunnah of the Prophet are stuck in the classic texts which binds progressive mindset of Muslims. Therefore, on the conditions and the present situation, the Sunnah of the Prophet can no longer be understood and applied textually (classic) and deemed to be immutable, but it must be understood and applied contextually following the appropriate methodology and its subject matters. This is a necessity, because the Sunnah status is different from the Koran. Thus, the Sunnah is always open to be developed, equipped and even modified, so its application is easy and doable.